Central and Peripheral Immunity Responses in Parkinson’s Disease: An Overview and Update - Ghaidaa Ebrahim; Hunter Hutchinson; Melanie Gonzalez; Abeer Dagra (Neuroglia, 2025)
Parkinson’s disease (PD) is a progressive neurodegenerative disorder characterized by motor and non-motor symptoms, with increasing evidence supporting the role of immune dysregulation in its pathophysiology. Neuroinflammation, mediated by microglial activation, pro-inflammatory cytokine production, and blood–brain barrier dysfunction, plays a crucial role in dopaminergic neuronal degeneration. Furthermore, peripheral immune changes, including T cell infiltration, gut microbiota dysbiosis, and systemic inflammation, contribute to disease progression. The bidirectional interaction between the central and peripheral immune systems suggests that immune-based interventions may hold therapeutic potential. While dopaminergic treatments remain the standard of care, immunomodulatory therapies, monoclonal antibodies targeting α-synuclein, and deep brain stimulation (DBS) have demonstrated immunological effects, though clinical efficacy remains uncertain. Advances in immune phenotyping offer new avenues for personalized treatment approaches, optimizing therapeutic responses by stratifying patients based on inflammatory biomarkers. This review highlights the complexities of immune involvement in PD and discusses emerging strategies targeting immune pathways to develop disease-modifying treatments.